Synthesis of Bi4Ti3O12/TiO2 Composite using Sonication Method - Istighfarini, Vina Nurul; Inggarwati, Ervina Dwi; Prasetyo, Anton (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2020)
Composite Bi4Ti3O12/TiO2 heterojunction photocatalyst has been prepared by sonication methods. The heterojunction material Bi4Ti3O12/TiO2 was synthesized using an ultrasonic cleaning bath for 4 hours, by mixing Bi4Ti3O12 and TiO2 with variations in the comparison of mol 1:1, 1:2, 1:4 and 1:6. Characterization with XRD showed heterojunction material consisting of Bi4Ti3O12, anatase, rutile, and Bi12TiO20. The surface was observed by SEM which showed the morphology of Bi4Ti3O12/TiO2 were spherical TiO2 and plate-like Bi4Ti3O12. The band gap energy of heterojunction material with a variation in mol Bi4Ti3O12: TiO2 of 1:1, 1:2, 1:4 and 1:6 are 3.09; 3.10; 3.15; and 3.16 eV respectively. The all of band gap energy is lower than the band gap energy of TiO2 anatase and higher than the band gap energy of Bi4Ti3O12.Keywords: composite photocatalyst, heterojunction, sonochemical, Bi4Ti3O12, TiO2.